2017
DOI: 10.1007/s40843-016-5170-2
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on intramolecular charge-transfer compounds as photoelectric active materials

Abstract: This article summarized the recent advance on the structural design and synthetic strategies of intramolecular charge-transfer compounds as well as their potential applications in two-photon absorption chromophores, organic photovoltaics and organic light-emitting diodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 51 publications
0
35
0
Order By: Relevance
“…The size of TPA is determined by its cross-section. It has been shown that linking the electron donor (D) to the electron acceptor (A) through a π-conjugated bridge and increasing the intensity and effective length of the π-conjugated bridge [ 1 , 20 , 21 ] result in a larger TPA cross-section. Simultaneously, when the intensities of the D and A are properly adjusted, the TPA is also strengthened.…”
Section: Introductionmentioning
confidence: 99%
“…The size of TPA is determined by its cross-section. It has been shown that linking the electron donor (D) to the electron acceptor (A) through a π-conjugated bridge and increasing the intensity and effective length of the π-conjugated bridge [ 1 , 20 , 21 ] result in a larger TPA cross-section. Simultaneously, when the intensities of the D and A are properly adjusted, the TPA is also strengthened.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10][11][12][13] Benefiting from their diverse advantages including well-defined structurald iversity,f lexibility and functionality,f ast response, and variable band gap, organic p-conjugated compoundsh ave been widely explored as NLO materials to enhance TPAa bsorption cross-sections. [14][15][16][17][18][19][20][21][22] In particular, extended p-conjugated systems with the symmetrical substitution of electron-donating and electron-accepting units have been regarded as efficient TPAm olecules to exhibit larger TPAa bsorption cross-sectionsc ompared to the corresponding unsubstituted counterparts, indicating that the efficient intramolecular charge transfer (ICT), [23,24] caused by the donating and withdrawing abilities of electron donor and acceptor,p lays an important role in increasing their TPAc ross-sectionsv alues. [25][26][27] Effortst of urtheri ncrease the nonlinearity are usually focused on enlarging the conjugation length or increasing the strength of donors or acceptors or both.…”
Section: Introductionmentioning
confidence: 99%
“…Organic molecules with high two‐photon absorption properties have attracted many scientists’ attention due to their potential applications in three‐dimensional (3D) fluorescence imaging, lasing up‐conversion, optical power limitation, photodynamic therapy and 3D optical data storage . Benefiting from their diverse advantages including well‐defined structural diversity, flexibility and functionality, fast response, and variable band gap, organic π‐conjugated compounds have been widely explored as NLO materials to enhance TPA absorption cross‐sections . In particular, extended π‐conjugated systems with the symmetrical substitution of electron‐donating and electron‐accepting units have been regarded as efficient TPA molecules to exhibit larger TPA absorption cross‐sections compared to the corresponding unsubstituted counterparts, indicating that the efficient intramolecular charge transfer (ICT), caused by the donating and withdrawing abilities of electron donor and acceptor, plays an important role in increasing their TPA cross‐sections values .…”
Section: Introductionmentioning
confidence: 99%
“…TADF emitters are the fluorophors with extremely small energy splittings (ΔE ST ) between the lowest singlet excited state (S 1 ) and the lowest triplet excited state (T 1 ), and thus they can enable efficient reverse intersystem crossing (RISC) process from T 1 to S 1 and utilize both singlet and triplet excitons for light emission [27,28]. Till now, the general design strategy for TADF emitters is connecting the electron-donor (D) and electron-acceptor (A) segments via a highly twisted structure to constrain the highest occupied molecular orbitals (HOMO) and lowest unoccupied molecular orbitals (LUMO) on D and A segments [29], respectively, which is essential to achieve an extremely small ΔE ST [30][31][32][33][34]. Based on such D-A structure, a large number of TADF emitters have been successfully developed and realized remarkable external quantum efficiencies (EQEs) even exceeding 20% [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%